Management of tuberculosis of the uterine cervix in the University Hospital Center of Treichville - J. M., Dia; T. C., Saki; Z., Kone; S., Koui; P. E., Bohoussou; A., Diallo; P., Guié; Anongba, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Genital tuberculosis is a rare entity which is classically presented with nonspecific signs posing diagnostic problems. We report the case of a young patient in genital activity, supported in our hospital for tuberculosis of the uterine cervix. She initially consulted for contact metrorrhagia and speculum examination had found an ulcerative budding cervix making suggest a cervical cancer. Finally, the histology of cervical biopsy confirmed the diagnosis of cervical tuberculosis and the patient was treated with anti-bacillary antibiotics. The evolution was favourable marked by declared healing after 6 months of treatment. The objective of this observation is to discuss the epidemiological, clinical and therapeutic characteristics of this affection.